Serum osteopontin as a prognostic biomarker in acute exacerbations of chronic obstructive pulmonary disease - Ma, Kai-Shu; Li, Li-Na; Ma, Yi-Cheng; Fan, Ru-Liu; Chen, Gang; Zhao, Hui; Qu, Kai-Xin; Fu, Lin (Frontiers in Immunology, 2025)
Osteopontin, a phosphorylated glycoprotein, is highly expressed in lung tissues and is elevated in inflammatory diseases. However, its role in acute exacerbation of chronic obstructive pulmonary disease (AECOPD) remains unclear. A total of 281 AECOPD patients, 89 stable COPD (SCOPD) cases, and 89 healthy volunteers were enrolled in this prospective cohort according to the inclusion and exclusion criteria. Demographic information and clinical features were obtained from electronic medical records systems. Fasting venous blood was collected on the day of admission, and baseline serum osteopontin was measured using an enzyme-linked immunosorbent assay. The primary endpoints—death, frequency of acute exacerbations, and hospital length of stay—were evaluated through a follow-up study. Baseline serum osteopontin levels were higher in AECOPD patients compared to SCOPD patients and healthy volunteers. Linear regression analysis revealed positive associations between serum osteopontin and severity scores in AECOPD patients, and an inverse correlation of serum osteopontin and pulmonary function in SCOPD patients. In addition, baseline serum osteopontin levels were elevated in AECOPD patients with poorer prognosis. Logistic regression analysis indicated that serum osteopontin was positively correlated with the risks of death and acute exacerbations in the first year. Receiver operating characteristic (ROC) curve analysis suggested that the predictive ability of serum osteopontin for poor prognosis was comparable to that of the COPD Assessment Test (CAT) score and superior to the modified Medical Research Council (mMRC) score among AECOPD patients. Our findings indicate that baseline serum osteopontin is positively associated with severity scores and adverse clinical outcomes, highlighting its potential value as a surrogate prognostic biomarker in AECOPD patients.